A Tale of Two Cemeteries: Dispatch, Smith and Jewell Counties, Kansas - Hocking, Jillian (Kansas State University. Dept. of History, 2011)
Located on the border of both Smith and Jewell Counties, tiny Dispatch was founded by the Dutch Reformed Church. When the church split along doctrinal lines, two cemeteries evolved for two different church populations. The main church was founded in 1871; the split occurred in 1872. The landscape of this area still reveals its early history. The bleak, flat prairies stretching around a large church and its two graveyards tell a tale of dissent and survival. The author, connected through family to these Dutch settlers, provides photographs and stories.
Keywords: Smith County; Jewell County; Dispatch; Dutch Reformed Church; Dutch cemeteries